Pay as you wish as a museum pricing mechanism - Crespo, Beatriz Vaz Serra (2019)
Currently, museums show difficulty in setting their ticket prices, as well as in increasing their revenue while remaining inclusive. Pay As You Wish is a pricing mechanism in which visitors are allowed to pay whatever value they wish for the museum visit, including zero. In order to evaluate if this pricing mechanism could be profitable in a museum while increasing inclusivity, online experiments were conducted to evaluate people’s willingness to pay. The results have shown that PAYW can be a profitable pricing mechanism in museum settings, translating into an increase of almost 40% in the museum’s return.